SLUM SETTLEMENT PHENOMENON IN MEDAN CITY (CASE STUDY: KAMPUNG AUR, MEDAN MAIMUN DISTRICT) - Yenny, Novida; Rohani, Rohani; Pinem, Kamarlin; Anggraini, Nabila (Universitas Negeri Medan, 2019)
Kampung Aur settlement is one of the slums of 18 villages determined based on Medan Mayor Decree No. 640/039.K / I/2015, with a very poor slum level, 3.49 Ha slum area and 307 households. Location Slums are scattered in various areas in Medan City, including along the river banks, along railroads, port areas, industrial areas, trade areas, and border areas of Medan City. The focus of the study was the slums of Kampung Aur, Medan Maimun District and the reluctance of residents to be relocated. The research objectives are; to find out the factors that cause the reluctance of relocation of residents of slums in Kampung Aur, Medan Maimun District, Medan City. The research method used a qualitative descriptive. The results of research on the reluctance of residents due to relocation of several factors, among others; 1) Settlement that has been passed down from parents has finally become the basis for residents to claim their legal presence in agararia, 2) the location of Kampung Aur which is near and downtown such as offices, restaurants and others that are very supportive for the economic activities of citizens, 3) the high family ties between residents supported by the same ethnic / ethnic origin, and a sense of shared destiny, 4) basic housing services that are deemed sufficiently adequate such as access to and out of villages, roads that connect between RTs, available clean water facilities, and electricity servis, 5) there are facilities and infrastructure that can meet the needs of citizens to socialize with each other and strengthen family relationships.Keywords: Slums; Settlement; Phenomenon.